MO233: Real-World Signs and Symptoms at Diagnosis in Patients With IGA Nephropathy. (3rd May 2022) - Roccatello, Dario; Kattlun, Julia; Przybysz, Raymond; Thomas George, Aneesh; Aldworth, Carolina; Proudfoot, Clare; Wang, Weijia; Decourcy, Jonathan; Lafayette, Richard
Abstract: BACKGROUND AND AIMS: Immunoglobulin A nephropathy (IgAN) is the most common form of primary glomerulonephritis worldwide, with an estimated annual incidence of 25 per million. Patients with persistent proteinuria ≥ 1 g/day are at increased risk of disease progression, with 30% or more progressing to kidney failure within 10 years. Hematuria and proteinuria are among the most common clinical manifestations of IgAN. The aim of this analysis was to better understand the clinical characteristics of IgAN patients from Europe, Asia and the USA, at the time of diagnosis. METHOD: A retrospective analysis was conducted using data from the Adelphi IgAN Disease Specific Programme (DSP), a cross-sectional survey of IgAN-treating nephrologists in EU4 (France, Germany, Italy, UK), USA, China and Japan between June and October 2021. Nephrologists completed structured forms administered via online links for successive patients presenting with IgAN in their practice. The forms included demographic and clinical information including signs, symptoms and lab values amongst others. RESULTS: A total of 269 nephrologists completed records for 1685 patients in this survey. Mean patient age was 43.3 years, and most were male (58%). The diagnosis was confirmed by biopsy in 86% of the patients. The mean eGFR at diagnosis ranged from 58.1 (median 55.5) in the USA to 78.3 (median 79.0) mL/min/1.73 m 2, in China and Japan. Mean proteinuria ranged from 2.7 (median 2.0) in the USA to 3.4 (median 2.1) g/day in EU4 (Table 1 ). The main clinical signs at diagnosis were proteinuria (75%) and visible hematuria (63%). Edema and fatigue were reported in 38% and 27% of patients; 10% and 9% of patients reported appetite loss and sleep problems. A sizable proportion of patients (31%) also experienced pain in various parts of the body. CONCLUSION: This comprehensive study of IgAN patients across varied geographies presents evidence that patients experience substantial symptomatic and clinical burden at diagnosis, irrespective of the region. The relatively high levels of proteinuria and low eGFR levels, especially in the USA, suggest that the disease is often severe and advanced by the time of diagnosis. Facilitating early diagnosis of IgAN—perhaps through better recognition of clinical signs and symptoms—could be beneficial in optimizing early treatment and preventing disease progression.